(3NeQI HGHd hZfGA GdHdGHd (B((3OjhGf TYQ(B)s - (3GdfGHdSj , YHO GdZfj Hf ESeGYjd Hf YHO GdZfj,J (B1143 (3g` s ((3Ydj GdHjQhJj s)
(3ChdgG (B:s
(3CeG HYO(B: (3ajbhd SjOj hGSJGPj GdTjN YHOGdZfj GdfGHdSj ef EfTGFg hbJ GedGFg hef GdeYdhe YfO Cgd GdYdhe Cf af GdCOH dWja aGFb heGA VMVGMg aj QjGV GdbQGFM QGFb s
(3BNQgG (B:s
(3hge Gdbhe HGdeYGQa bGehG hdge HGdYdhe cGS dG Jbdj(B: (3ef ge age aj GdJLdj Ef ageJge ge GdLHGd GdQhGSj s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B271s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B291 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs